2021
DOI: 10.3390/ijms22073453
|View full text |Cite
|
Sign up to set email alerts
|

Successful Partnerships: Exploring the Potential of Immunogenic Signals Triggered by TMZ, CX-4945, and Combined Treatment in GL261 Glioblastoma Cells

Abstract: Background: The relevance of the cancer immune cycle in therapy response implies that successful treatment may trigger the exposure or the release of immunogenic signals. Previous results with the preclinical GL261 glioblastoma (GB) showed that combination treatment of temozolomide (TMZ) + CX-4945 (protein kinase CK2 inhibitor) outperformed single treatments, provided an immune-friendly schedule was followed. Our purpose was to study possible immunogenic signals released in vitro by GB cells. Methods: GL261 GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…The beneficial effect of TMZ in preclinical/clinical settings was mainly attributed to its effect as DNA alkylating agent and activation of the apoptotic cascade [ 49 , 50 ]. However, it is worth noting that TMZ alone has a cytostatic rather than cytotoxic mechanism, when added to GL261 cultured cells at concentrations similar to the ones used in preclinical studies, as described in [ 9 , 51 , 52 , 53 ]. Thus, the main beneficial effects observed with TMZ therapy may have a different explanation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of TMZ in preclinical/clinical settings was mainly attributed to its effect as DNA alkylating agent and activation of the apoptotic cascade [ 49 , 50 ]. However, it is worth noting that TMZ alone has a cytostatic rather than cytotoxic mechanism, when added to GL261 cultured cells at concentrations similar to the ones used in preclinical studies, as described in [ 9 , 51 , 52 , 53 ]. Thus, the main beneficial effects observed with TMZ therapy may have a different explanation.…”
Section: Discussionmentioning
confidence: 99%
“…At the therapy starting point, GL261 GB tumours display an essentially protumoural microglia/macrophage phenotype, supported by qPCR results and encoded in the red colour over the tumour mass of the nosological images. TMZ therapy may lead to release/exposure of immunogenic signals [ 53 ], which set the cancer immunity cycle [ 59 ]. In the meanwhile, both M1 and M2 populations increase (see also Figure 2 A): M1 microglia/macrophages will participate in tumour cell killing [ 9 ], and M2 microglia/macrophages are waiting for M1 polarisation.…”
Section: Discussionmentioning
confidence: 99%
“…GL261 cells are moderately immunogenic and suitable for orthotopic implantation in syngeneic and immunocompetent animals to study tumor immunology [ 39 , 41 ]. For instance, glioma GL261 cells were used to study the mechanisms of immunogenicity of cell death in response to various anti-cancer therapeutic agents, including to chemotherapeutics and photodynamic therapy [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy can lead to type II programmed cell death and evidence suggests that autophagy may be important in the treatment of GBM [ 60 , 61 ]. Autophagy promoting drugs, such as temozolomide, can selectively kill apoptosis-resistant glioblastoma cells [ 62 , 63 ]. In this study, we found that treatment with taxifolin increased the expression of autophagy-related proteins including LC3B-II, Atg7, atg12, and Beclin-1 suggesting that the autophagic pathway was activated in our tumor model.…”
Section: Discussionmentioning
confidence: 99%